Urbanization impact assessment on environment and transportation perspectives: Remote sensing-based approach application - Mhana K.H.; Norhisham S.; Katman H.Y.B.; Yaseen Z.M. (Elsevier B.V., 2025)
Environmental impact assessment of urbanization and road network analysis are more essential for city's health measurement. Road contraction due to high urbanization is more impactful for the ecology and traffic congestion-related phenomena. Remote sensing (RS) is a highly applied approach for analyzing the environmental and road cities network-related activities. Landsat 5 TM and 8 OLI/TIRS databased and recent time road network information were used and aimed for assessment of different cities (i.e., Baghdad ?Iraq? and Los Vegas ?United States?). The Land use and land cover (LULC) and road network are related to each other's due to the high urbanization and population pressure. Based on modeling results, built-up zones of the selected cities were increased by 249.84 km2 (Baghdad) and 728.47 km2 (Los Vegas) while barren land fluctuated 396.85 km2 (Baghdad) and ?712.58 km2 (Los Vegas). Based on the studied period, land surface temperature (LST) increased by 8.68 C (Baghdad) and 10.06 C (Los Vegas), which indicates the urbanization effects. Road density observed to be high in the central part of the Baghdad city, while Los Vegas have road density in the entire region. Both cities showed low content of water bodies and vegetation due to urbanization and population pressure. In general, both cities need proper adaptation strategies, urban planning, novel approaches, and management that can help for reduction of the environmental impact. In addition, cities road network-related issues could be substantially increased due to unplanned traffic congestion, accident, environmental degradations in which is triggering the urban vulnerability in near future. ? 2024